2006
DOI: 10.1007/s11258-006-9147-y
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Metapopulation Dynamics to Two Different Kinds of Habitat Destruction Caused by Human Activities

Abstract: Habitat destruction can be classified into instantaneous destruction and continuous destruction by the different ways of human destroying habitat. Previous studies, however, always focused on instantaneous destruction. In this study, we develop a universal model, Multitime scale N-species model, to study and compare the responses of metapopulation dynamics to both kinds of habitat destruction. The model explores that: (1) under instantaneous habitat destruction, species extinction is determined by the proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Despite some criticism (McCarthy et al, 1997), the metapopulation model developed by Tilman et al (1994) remains an important tool for exploring consequences of habitat loss in multi-species communities with competition (Loehle and Li, 1996;Stone et al, 1995;Stone et al, 1996;Klausmeier, 1998;Lin, 2005;Liu et al, 2007). In this paper, we address the issues related to succession in species abundances in such habitats: alterations of the abundance ranking, changes in the rank-abundance curve, variation in species evenness and diversity (see below).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite some criticism (McCarthy et al, 1997), the metapopulation model developed by Tilman et al (1994) remains an important tool for exploring consequences of habitat loss in multi-species communities with competition (Loehle and Li, 1996;Stone et al, 1995;Stone et al, 1996;Klausmeier, 1998;Lin, 2005;Liu et al, 2007). In this paper, we address the issues related to succession in species abundances in such habitats: alterations of the abundance ranking, changes in the rank-abundance curve, variation in species evenness and diversity (see below).…”
Section: Discussionmentioning
confidence: 99%
“…Those species are often supposed to be strongest competitors due to the so-called competitioncolonization trade-off (Klausmeier and Tilman, 2002). Later works (Lin, 2005;Liu et al, 2007) pointed out, as well, the importance of some other issues: the existence of a minimal threshold p 0 of abundances and the influence of transition time from an intact habitat D ¼ 0 to a habitat with D ¼ D * 40.…”
Section: Introductionmentioning
confidence: 99%
“…The persistence of natural populations faces three challenges: habitat destruction, climatic change and biological invasion, which are all human associated [1]. Studies have shown that species disappear up to 1000 times faster than without anthropogenic disturbance [2]. Among these challenges, habitat destruction has been suggested to be the foremost cause of species extinction [3][4][5].…”
Section: Introductionmentioning
confidence: 99%